Yritsten kansainvälistymisen vaikutukset kotimaan talouteen ja työllisyyteen: Katsaus kirjallisuuteen - Annu Kotiranta; Sarianna M. Lundan; Pekka Ylä-Anttila (The Research Institute of the Finnish Economy (ETLA), 2008)
This report reviews some of the most recent literature examining the home country employment effects of internationalisation. A brief overview of the history of the internationalisation of Finnish firms is also presented. The general conclusion from the literature is that the absolute employment effects are modest, although there are likely to be notable effects on the structure of labour demand. However, the form of internationalisation, the level of aggregation of the data, and differences in labour market institutions all have an influence on the results. Most of the studies looking at the employment effects of outward foreign direct investment on the home country seem to indicate positive rather than substitution effects. On the other hand, when looking at the effects of offshore outsourcing, the results are ambiguous.
Keywords: F16; F14; F23; J23; J63; 330; internationalisation; FDI; outsourcing offshore; employment; labour market; Multinationales Unternehmen; Direktinvestition; Offshoring; Beschäftigungseffekt; Finnland